Letramento digital: as práticas de escrita nas plataformas digitais e o processo de aprendizagem na escola. - Austregésilo, Veralúcia Maria de Andrade França (2020)
Contemporary Society is involved in digital ambience, the family, the school, the work and everything that surrounds tasks and social living are connected by an irreversible technological link. Digital literacy culture, through writing practice on digital platforms is responsible for this huge progress in communities lives, mainly, with a relation in the way, dynamics and speed of communication. This present research aimed to analyze digital writing practice, through Instagram and its contributions for digital literacy and the relation between the teaching learning process on final years on elementary school on Sistema educacional Radar in the city of Vitória de Santo Antão. The experiment was performed with students in a restrict and private group on Instagram where texts and other materials were posted with other courseware such as images and videos in order to create interaction. These dialogues were classified as types and levels of language and globally analyzed and by post object. Overall results in terms of levels (informal: 35,70%, formal: 41,48%, artistic: 22,19% and technician: 0,63%) and types ( verbal: 47,46%, non-verbal: 36,94%, verbal and nonverbal: 15,60%) of language used in posts presented a hybrid language. As perceived, this type of communication that occurs on social networks has a colloquial profile that thinking in the field of language and the production of digital text, exclusively as something formal, may still be far from the interest and feeling of these subjects (students), however, providing more motivating practices (use of Instagram) in educational practices, ends up being important in this hyperconnected class that has nothing passive about knowledge.